Peningkatan Nilai Tambah Melalui Produk Holtikultura Sayuran Bayam, Kangkung dan Terong di Dusun Bangko Jailolo Selatan Kabupaten Halmahera Barat - Nurdiyanawati Djumadil; Natal Basuki; Mardiyani Sidayat; Karmila Ibrahim; Mila Fatmawati; Fatmawati Kaddas; Haris Mahmud (BARAKTI: Journal of Community Service, 2023)
Water spinach (Ipomea reptans Poir) is one of the most popular horticultural crops favored by the people of Indonesia because of its savory taste. There are several varieties of spinach, including regular green spinach, red spinach, snapper spinach, thorn spinach and Kotok or Tanah spinach. The types of spinach that are often cultivated are Amaranthus tricolor and Amaranthus hybridus. The purpose of this community service is to understand the farming community in product development from spinach, kale and eggplant. This PKM activity applied several methods, including carrying out counseling about the importance of making chips from spinach, kale and eggplant itself. Next, a demonstration of making spinach, kangkong and eggplant chips. The results of community service can be interpreted: (1) Community service activities have a high and enthusiastic response from the farming community to all activities that have been designed by the service team; (2) It is hoped that the impact of the training in providing skills provision on various materials that have been provided will motivate the formation of home businesses (home industries) that can increase family income